PENGARUH HARGA, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA PT JOLIN PERMATA BUANA - Aisyah, Assalamah; Wasiman, Wasiman (LPPM Universitas Putera Batam, 2019)
The rapid development of housing in the city of Batam make to community more and more choose to choose the criteria of occupancy in want. This makes the competition among developers increasingly tight, in because of increasingly fierce competition companies to complete to attract consumers to choose their products. This study aims to determine the effect of price, product quality and service quality to purchase decisions. The sample used was 100 respondents with incindental sampling method. Data processing using descriptive analysis and multiple linear regression analysis processed with the help of SPSS program 21. The results showed all the data valid and reliable. From t test result known that t count for variable price (X1), product quality (X2) and service quality (X3) > t table 1,983 with significance < 0,05. So the first hypothesis, the second hypothesis, and the third hypothesis are accepted. The f shows F arithmetic > 2,70 and significance < 0,05 this the fourth hypothesis is accepted.